Attitude towards Advertising: A Comparison between Marketing and Non-marketing Students at a Private University - Ernest Cyril, de Run; Hiram, Ting; Jee, Teck Weng; Sally, Lau Yin Choo (2013)
The purpose of this study is to determine general attitude towards advertising from the perspective of marketing and non-marketing students. Beliefs towards advertising are investigated so as to determine what contributes to attitude and subsequently behavioral intention towards advertising. A quantitative approach by means of questionnaire based survey was administered at a private university. 217 usable copies, whereby 101 are marketing students and 116 are non-marketing students, were collected. Descriptive and inferential analyses were subsequently used. Findings show that there is no significant difference in beliefs, attitude and intention towards advertising among marketing and non-marketing students despite dissimilar educational background. This study therefore articulates the present view of university students about advertising, and its implication to academia and business.